Effect of Expressive Writing on the Subjective Well-Being of University Students - Cayubit, Ryan Francis O. (Makara Human Behavior Studies in Asia, 2021)
The main intent of this research is to test the effectiveness of expressive writing in processing and dealing with inhibited emotions of university students. The use of expressive writing targets the subjective well-being of the subjects, specifically their happiness and life satisfaction. Employing a between-subjects design, a thorough and rigorous psychological experiment was performed on 23 student volunteers where expressive writing was designated as the independent variable and happiness and life satisfaction as dependent variables respectively. Results of the non-parametric analysis showed that after the experimentation, both the happiness and life satisfaction of the subjects improved. Theoretical implications of the study are discussed in this paper.